Potensi infusa daun belimbing manis (Averrhoa carambola l.) sebagai diuretik pada mencit jantan galur BALB-C - Dyah Anggraeni; Nuzulia Sari Asyifa (STIKes Surya Global Yogyakarta, 2020)
Hypertension is a disease that many Indonesians suffer from. One of the drugs for hypertension is diuretics, which can increase urine output through direct action on the kidneys. Sweet star fruit leaves (Averrhoa carambola L.) are one of the medicinal plants that can be efficacious as a diuretic. This study aims to determine the diuretic potential and determine the effective dose of sweet star fruit leaf infuse. The test animals used were 25 Balb-C male white mice. Diuretic testing is done by measuring the volume of urine released for 2 hours after treatment. Test animals were fed for approximately 16 hours, then divided into 5 groups. The normal control group was given 0.5% CMC solution as much as 0.5 ml, the positive control group was given furosemide 7.25 mg/KgBB mice, the first dose test group was given sweet star fruit leaf infuse 625 mg/KgBB mice, the second dose test group was given sweet star fruit leaf infuse 1,250 mg/KgBB mice and the third dose test group was given sweet star fruit leaf infuse 2,500 mg/KgBB mice. The results showed that the effective dose of sweet star fruit leaf infuses was found in the third dose with an average of 1.178 ml and close to the urine volume of the positive control group which was 1.434 ml. Data were analyzed statistically using the One Way ANOVA method with a confidence level of 95%. The results of the analysis showed that the administration of sweet star fruit leaf infuses gave a significant difference in the diuretic effect compared to the normal control group.